2003
DOI: 10.1038/sj.bmt.1704271
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia with the onset of graft versus host disease

Abstract: Summary:Pure red cell aplasia (PRCA) occurred in the fourth month after an ABO-compatible nonmyeloablative allograft coincident with the cessation of immunosuppression and the onset of limited chronic GVHD. No secondary causes could be identified. Erythropoiesis was restored promptly and durably with the resumption of immunosuppression. A clonal T cell receptor c rearrangement was detected in peripheral blood lymphocytes prior to the onset of PRCA. PRCA should be added to the list of immunohaematological compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Moreover, although several case reports suggested such an association, it was not confirmed by any of the case series. 30,49 In support of the findings of Mielcarek et al, we observed that both the occurrence of acute GvHD and isoagglutinin reduction were associated with a shorter time to RBC engraftment in patients with major ABO incompatible HSCT. In contrast, faster RBC engraftment in patients who underwent GvHD was not observed after ABOidentical HSCT (data not shown).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, although several case reports suggested such an association, it was not confirmed by any of the case series. 30,49 In support of the findings of Mielcarek et al, we observed that both the occurrence of acute GvHD and isoagglutinin reduction were associated with a shorter time to RBC engraftment in patients with major ABO incompatible HSCT. In contrast, faster RBC engraftment in patients who underwent GvHD was not observed after ABOidentical HSCT (data not shown).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 80%
“…25 Major ABO-incompatibility was the most common risk factor described in 120 patients, bidirectional ABO incompatibility was found in 5 patients. 16,25,37 Two of the remaining three patients developed PRCA after ABO compatible HSCT 41,49 and one after autologous HSCT. 39 No clear explanation was found for the PRCA in these patients.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that donor antibodies can target recipient RBC antigens, especially in cases of ABO incompatibility, and that this can result in selective hemolysis of recipient RBC and RBC precursors. 15,16 GVHD can also target recipient hematopoietic stem cells. [17][18][19][20][21] However, none of the patients in this report had evidence of immune-mediated hemolysis despite the presence of ABO incompatibilities in 6 of the 8 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, PRCA can occur as a manifestation of cGVHD specifically. 1,4 Furthermore, A/O donor/recipientmismatch has been associated with a particular increase in the risk of development of PRCA post PBSCT. 5 A growing body of literature supports a role for rituximab as a therapy for cGVHD.…”
mentioning
confidence: 99%